2011
DOI: 10.4269/ajtmh.2011.10-0728
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Polymorphisms in Dengue Virus–Infected Children

Abstract: Abstract. Differential viral recognition by cells bearing Toll-like receptor 4 (TLR4) polymorphisms Asp299Gly and Thr399Ile may influence susceptibility and severity of dengue virus infection. In central Java, Indonesia, we investigated 201 children with dengue hemorrhagic fever (DHF) and 179 healthy controls. Patients and controls were mostly ethnic Javanese. A nearly complete cosegregation of the two mutations was observed. The TLR4 299/399 genotype was found in five patients and four controls. Prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…Similarly, Gly allele (Asp299Gly) and Ile allele (Thr399Ile) frequency were higher in DF cases compared to control subjects (19.1% vs. 11.0% and 11.1% vs. 5.0%, respectively). However, a study from Indonesia showed that children with severe dengue case presentation (DHF/ DSS) did not show any association with TLR4 Asp299Gly and Thr399Ile polymorphisms which corroborates with the result of present study (Djamiatun et al, 2011). We also found the lower expression of TLR4 mRNA in severe cases (DHF/DSS) compared to non-severe (DF) cases.…”
Section: Discussionsupporting
confidence: 95%
“…Similarly, Gly allele (Asp299Gly) and Ile allele (Thr399Ile) frequency were higher in DF cases compared to control subjects (19.1% vs. 11.0% and 11.1% vs. 5.0%, respectively). However, a study from Indonesia showed that children with severe dengue case presentation (DHF/ DSS) did not show any association with TLR4 Asp299Gly and Thr399Ile polymorphisms which corroborates with the result of present study (Djamiatun et al, 2011). We also found the lower expression of TLR4 mRNA in severe cases (DHF/DSS) compared to non-severe (DF) cases.…”
Section: Discussionsupporting
confidence: 95%
“…This could be important in the neonatal response of Mo/MF to DENV, since this virus has been shown to induce the translocation of HMGB1 from the nucleus to the cytoplasm in human monocytes, which is followed by further proinflammatory events (24). In addition, monocytes and T-lymphocytes from neonates are capable, like those from adults, of recognizing the presence of pathogens through Toll-like receptors (TLRs) (8), and these receptors play a role in the susceptibility and severity of complicated DENV infection (10). The clinical relevance of the observed decreased IL-1b, IL-6, and TNF-a production in neonatal Mo/MF remains to be clarified, since several studies have shown that dengue shock syndrome is rare in neonates (6), and this condition has been related to increased circulation of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…It was contrast with previous studies that the polymorphism TLR4 Asp299Gly gene was associated with susceptibility and severity of gram negative infections 5,10 . Other studies showed similar result that there were no significant differences of TLR4 Asp299Gly between DHF/DSS and control group, or severity of meningococcal infection and outcome of gram negative sepsis [20][21][22][23] . Metaanalysis studies in Caucasian and in China found that there were not strong correlation between sepsis and TLR4 Asp299Gly polymorphism [24][25][26][27] .…”
Section: Discussionmentioning
confidence: 58%